CRITICISM: SPIRIT OF TIME, SPIRIT OF ANALYSIS OR BEING OF CONSCIOUSNESS AND SOUL?!.. - Horob, S. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the important problem of specific and actualization of functionality of literary criticism, its methodological bases and new signs is broken in modern literature process. It is taken away in the title of original poliaspect variety her nominate, certainly, in no way foresees certain regulation herein, and probably induces to the polemic and discussions - both historical and literary and theoretic-methodological.